Non-operative methods for the treatment of female stress urinary incontinence - Wojciechowska, Klara; Turek, Monika; Skotnicka, Joanna; Jaroń, Aleksandra; Jastrzębska, Katarzyna; Piątkowska, Karolina; Błaszczak, Karolina; Witkowska, Maria; Ślósarz, Tymoteusz; Witkowski, Maciej (Quality in Sport, 2024)
Purpose of research: Stress urinary incontinence (SUI) is a common health problem, especially among women which impairs daily functioning. The purpose of this research is to elucidate the pathophysiology of stress urinary incontinence (SUI), describe its diagnostic methods, summarize current treatments in light of recent studies, and outline examples of new potential therapies. Methods: Databases such as PubMed, Medline, and ResearchGate were searched with particular attention to the current guidelines. Basic results: The primary treatment of SUI is lifestyle modification, including weight reduction. Pelvic floor muscle training (PFMT) is recommended as first-line therapy, reducing the number of incontinence episodes and improving quality of life. Additional methods include electrical stimulation or biofeedback. At later stages of treatment, pharmacological therapy is recommended, mainly using vaginal oestrogens and duloxetine. Conclusions: Non-operative therapies, such as lifestyle modification and PFMT, are effective treatments for SUI. In combination with pharmacotherapy, they significantly improve the quality of life of patients without invasive surgical procedures.